How New Business Models Shape Innovation Spillovers: Insights from the New Space Economy - Lars Hornuf; Daniel Vrankar (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Those seeking to drum up public support for the space industry frequently cite its potential to generate valuable spillovers to other industries. However, existing research on spillover effects overlooks differences in business models among commercial actors and focuses only on individual projects or specific space agencies. We analyze how evolving business models influence spillovers by comparing the dynamic capabilities of traditional aerospace conglomerates to those of new space firms, using a unique dataset of 35,696 space-related patent applications. We find that, in addition to industries directly related to space, such as aeronautics, sectors like manufacturing and communication technology in particular benefit from space activities. At the firm level, we observe that new space business models present greater spillover potential and generate more spillovers than traditional aerospace conglomerates. However, traditional conglomerates such as Airbus or Boeing induce spillovers into digital systems and clean tech, while new space firms cannot translate their digital business models into digital spillovers and occupy more peripheral positions in the innovation network of space. Additionally, based on two different innovation metrics and more than 1.6 million additional patent applications, we find no evidence that the business models of the space industry have generally led to more spillovers than other high-tech industries.
Keywords: D62; H57; L20; L21; 330; new space business models; new space economy; innovation; dynamic capabilities; spillover; patent data